CAMELLIA THUANANA (CAMELLIA SECT. CHRYSANTHA) – A NEW SPECIES FROM THE CENTRAL HIGHLANDS, VIETNAM - Thanh Truong Hoang; Hong En Le; Thi Lieu Nguyen (Tạp chí Khoa học Đại học Đà Lạt)
Camellia thuanana, a new species of the genus Camellia L. (Theaceae) is described and illustrated from the Central Highlands, Vietnam. Morphological features of this species are small flowers and pedicellate; leaves stalked, anastomosing venation, blades oblong-elliptic to elliptic, sparsely hirsute along the midrib below; pedicel very short; bracteoles 2–3, triangular; sepals 4–(5) in opposite pairs; corolla light greenish-yellow color; petals 7–8, glabrous; androecium 190–200 stamens, light yellow, in 3–4 circles; gynoecium 3, ovary ovoid and pubescent; styles 3, free to the base, and glabrous. C. thuanana resembles C. thuongiana in some morphological characteristics. C. thuanana is classified into sect. Chrysantha by styles completely free, flowers yellow, ovaries 3–5 locular, and partially connate. The IUCN Redlist Category of C. thuanana was assessed as Critically Endangered (CR).